Dental Seminars: developing knowledge, research and critical thinking (Research, Society and Development, 2021)
The dental seminar is an integral education system, which allows the student enriching knowledge of different subjects, in addition to providing adequate forms of interdisciplinarity. The objective is to provide the student with a better resource in the elaboration, presentation and oratory of seminars, promoting the ability to research and systematize the facts, reasoning and reflection around issues in the dental area. Moreover, the development of seminars allows the improvement of the ability to speak in public and reduce anxiety, with a consequent improvement in performance. Therefore, this work aims to report the experience of the activity developed by the Tutorial Education Program (PET) of the Dentistry course at the State University of Maringá, which aims to complement the training of the student, called “Dental Seminars”. PET members are organized into groups for the development of seminars. The activity is open to the entire academic community and its propagation is carried out through our social networks. Petians, through the presentation of the seminars, seek to guarantee an interdisciplinary and complete training, interacting with guests and teachers, increasing interest and knowledge on various dental issues. Still, there is the development of a critical view from the experience of an evaluation board. It is possible to say that interdisciplinary actions provide differentiated experiences in an innovative teaching and learning scenario. This context contributes to the training of future dentists, prepared to carry out activities in a humanized way and interconnected with the capacity for greater skill in presenting to the public.